MATERNAL EMERGENCY REFERRAL CASES THROUGH SIRESIK CALL CENTER DATA - Neni Nuraeni; Ida Herdiani; Yusuf Romli (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2022)
The government's efforts in reducing maternal and infant mortality by utilizing technological advances to allow users to communicate more quickly, effectively, and efficiently, Tasikmalaya Regency launched an Effective Referral Information System program to Save Mothers and Families called SI RESIK. But in fact, maternal emergency cases are still late to be handled, the cause is incomplete data during making referrals. Incomplete data will affect the potential fatality and access to advanced health facilities (FKTL). The purpose is to provide information related to the data in SIRESIK to describe the emergency referral situation in Tasikmalaya Regency which can be followed up for improvement of emergency case referral services to reduce maternal and infant mortality. Quantitative description research methods with quantitative data collected through SI RESIK call centers from January-December 2019 include varibel referral cases, referral hospitals, blood types, time response, funds guarantee. The data was analyzed using frequency distribution. The results of the most referral cases of maternity mothers (59.39%), the most referral hospitals SMC Hospital (64.18%), blood type unknown (62.87%), and response time 5-10 minutes (78.18%), guaranteed funds recipients (42.18%). Many emergency cases were not handled quickly because they have to complete the data to meet the requirements for case referral to advanced facilities. Keywords: SI RESIK Call center, emergency, maternal, referral.